SUSTAINABLE GOAT BREEDING AND GOAT FARMING IN CENTRAL AND EASTERN EUROPEAN COUNTRIES - Vladimir Dzabirski, Koco Porcu, Dragoslav Kocevski, Mirjana Jankulovska and Goran Trajkovski (My University, 2014)
Principal component analysis (PCA) and cluster analysis were performed to describe and understand the extent of genetic variability in domestic Balkan goat ecotypes from The former Yugoslav Republic of Macedonia. In this study, goat ecotypes from ten different farms/locations were analysed to determine the uniqueness of the domestic Balkan goat breed and evaluate the level of diversity among ecotypes. A total of 1 129 animals of both sexes were characterized according to 18 qualitative traits. The frequencies of each analysed trait for each ecotype were determined and used in PCA and cluster analysis. The first two principal components explained 94 percent of the total variance in this data set. All ecotypes except ecotypes 5 and 6 were significantly correlated with principal component 1 (PC1). These findings were confirmed by cluster analysis. Based on the obtained results, two main clusters were identified. The first cluster comprised ecotypes 5 and 6 while ecotypes in the second cluster were classified into two subclusters. This study provided initial information on the extent of genetic variability in Balkan goat ecotypes from the country. However, for better characterization and assessment of genetic diversity in the analysed goat population, further evaluation is recommended, based on both morphological and molecular markers.
ASSESSMENT OF GENETIC DIVERSITY IN DOMESTIC BALKAN GOAT ECOTYPES IN THE FORMER YUGOSLAV REPUBLIC OF MACEDONIA
Keywords: goat ecotypes, genetic variability, principal component analysis, cluster analysis